The Economics of U.S. Multinational Group Audits: Evidence from PCAOB Data - Downey, Denise Hanes; Kitto, Andrew R.; Bedard, Jean C. (The Accounting Review, 2026)
ABSTRACT Macroeconomic forces are challenging the ability of audit firms to sustain engagement profitability. Although one available strategy for multinational clients is to employ non-U.S. firms as component auditors (CAs), the impacts of this choice are unclear. We investigate the influence of CAs on engagement economics in Big 6 audits from 2012 to 2022, a period of increasing non-U.S. labor use. Results show that global hours increase with CA participation, suggesting that additional CA labor is needed to substitute for each U.S. hour. Global billing rates decline, implying that principal auditors share savings from lower cost labor with clients. However, U.S. lead team realizations rise with increasing substitution of non-U.S. labor, incentivizing more extensive CA use. Further analysis shows that these impacts are concentrated in engagements with high CA participation in countries with low wages and low English proficiency. Audit quality is not reduced by greater substitution of non-U.S. labor. JEL Classifications: M40; M42; M48; F66.